Age at menarche and its association with the metabolic syndrome in Taiwan. (September 2016) - Chang, Chia-Jung; Lai, Ming-May; Lin, Cheng-Chieh; Liu, Chiu-Shong; Li, Tsai-Chung; Li, Chia-Ing; Lin, Wen-Yuan
Summary: Background: The average age at menarche in the Taiwanese population is falling. Contrarily, the prevalence of metabolic syndrome (MetS) showed a worldwide increase in the past two decades. The aim of this study was to examine the association between age at menarche and MetS. Materials and methods: A total of 3292 women aged 19–91 years old were enrolled in two databases from 2004 to 2008. MetS was defined according to American Heart Association's criteria. Age at menarche was obtained from self-reported questionnaires. Multiple logistic regression analyses were used to estimate the association between age at menarche and MetS with adjustment for potential confounding variables. Results: The prevalence of MetS increased with age. After adjusting age, lifestyle status, and reproductive factors as variables, subjects who had menarche at a younger age showed significantly higher risk of MetS. The adjusted odds ratio of having MetS in <12 and 12–14 years old menarche age groups were 1.71 (1.07–2.71) and 1.22 (1.00–1.50), respectively. The significant increase in odds ratio for MetS in early age menarche also reveals a dose–response effect. Conclusions: Early onset of menarche is an important risk factor of MetS and may help identify women at risk of MetS.